Time-of-day modulation in mosquito response persistence to carbon dioxide is controlled by Pigment-Dispersing Factor - Linhan Dong; Richard Hormigo; Jord M. Barnett; Chloe Greppi; Laura B. Duvall (Proceedings of the National Academy of Sciences, 2025)
Each year, hundreds of millions of people are sickened by diseases that are transmitted through mosquito bites, including dengue, Zika, and malaria. Mosquito biting does not occur uniformly throughout the day and peak biting times follow species-specific patterns. While host-associated cues, like carbon dioxide (CO 2 ), behaviorally activate human-biting mosquitoes to search for a host, the mechanisms that regulate these responses throughout the day remain poorly understood. Here, we introduce an automated behavioral tracking system to investigate time-of-day variation of CO 2 responsiveness in Aedes aegypti . We find that while acute responses to CO 2 remain consistently high throughout the light phase, response persistence peaks only at dawn and dusk, in alignment with field-observed biting rhythms. We identify the circadian neuropeptide Pigment-Dispersing Factor (PDF) as a key regulator in the daily timing of spontaneous locomotor activity and CO 2 response persistence. Mosquitoes lacking PDF show reduced activity and CO 2 persistence in the morning. In response to a blood meal baited with heat and human odorants, pdf mutants also show reduced feeding in the morning and midday. Additionally, loss of pdf impacts the spatial pattern of PDF immunostaining and cell-autonomous clock gene oscillation in the central circadian system. Notably, acute CO 2 responsiveness remains rhythmic without external zeitgeber cues and is unaffected in pdf mutants, suggesting distinct regulatory mechanisms for acute CO 2 activation versus response persistence. These findings reveal a circadian layer of control of mosquito activity pattern that temporally modulate host-seeking drive.